IMPLEMENTASI PROGRAM PENANGGULANGGAN PRAVELANSI STUNTING ANAK BALITA PADA DINAS KESEHATAN KABUPATEN KONAWE - La Ode Muhammad Elwan; Rahman Rahman; Elsa Fitri Cahyani (Journal Publicuho, 2022)
This study aims to determine the implementation of the stunting prevalence prevention program for children under five and to find out the factors that influence the implementation of the stunting prevalence prevention program for children under five at the Konawe District Health Office. This study uses a qualitative approach, primary data sources from informants are then analyzed using analysis techniques according to Miles Huberman. The results 1of this study indicate that the implementation of the Prevention of Childhood Stunting Prevention Program at the Konawe District Health Office is firstly complete basic immunization in the Stunting Prevention Prevention program is maximum and has been realized well, Second, the field of providing additional food to children under five, in general, is 1in accordance with the provisions set forth in this study. Is hoped that, Third, it can be said that the implementation of the Stunting Prevalence Prevention program is very important so support from the local government and the central government is needed. Fourth, the field of zinc provision has been realized properly and efficiently through socialization and data collection for the people of the Konawe Regency. Factors influencing the implementation of the stunting prevalence prevention program in the areas of communication, resources, disposition, and bureaucratic structures have not worked well due to the difficulty of the telephone network and many people living in remote areas, making it very difficult to communicate as well because of the damaged road conditions making it difficult. prevention of stunting prevalence to the people of Konawe Regency